Analysis ofWIMAX performance at link-level - Hагорнюк, О. С. (Problems of Informatization and Control, 2008)
<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Link-level simulation methodology for WIMAX was considered to examine the behavior of single link<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">under different conditions. These results can be used to find potential advantages of various PHY<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">characteristics, such as structure of receiver and multi antennas methods at different conditions. Also<span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="font-size: 13.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">results of WIMAX performance in fading channels were obtained